Avaliação da aprendizagem de alunos com deficiência: estudo documental das diretrizes oficiais - Fernandes, Tereza Liduina Grigório (2010)
The present study aimed to investigate, in documents from Brazilian Ministry of Education, guidelines regarding the learning evaluation of students with disability registered in Regular Education. Specifically, aimed to identify the conception of learning evaluation officially recommended for those students as well as recognize the evaluation strategies according to a proposal of Inclusive Education. Historically, a gradual evolution is verified from exclusion and segregation to the socioeducacional inclusion of people with disability. After political, social and educational pressures, countless legal measures were elaborated, national and internationally, to assure the fundamental right to education for those people. The Education constitutes an indispensable way to combat inequality and to promote the social and education inclusion of people with disability. For students with disability, the learning evaluation presents complex characteristics, because of their specificities. The inexistence of an appropriate evaluation collaborates to validate prejudices against that population. The main purpose of the learning evaluation should consist of analyzing the potentialities of development and learning of the students with disability, thinking about the necessary education resources in benefit of their learning. In that sense, it was proceeded a research of documental nature, and the object of study was constituted by documents of national expression in the area of Inclusive Education, with circulation among teachers and searchers of the subject. Therefore, publications of the Collection Saberes e Práticas da Inclusão and Inclusão: Revista da Educação Especial, organized for the General Office of Special Education with support of Brazilian Ministry of Education, from 2005 to 2008, were analyzed. The content analysis accomplished identified the following themes: i) models of learning evaluation; ii) objectives of learning evaluation; iii) planning of the evaluation; iv) evaluation instruments. The investigated official documents present a general proposal about evaluation strategies for Inclusive Education, although they emphasize actions for deaf people and people with intellectual disability. They consider the formative evaluation the most appropriate model for the learning evaluation of people with disability in Inclusive Education.